2010
DOI: 10.3109/09637486.2010.532116
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of cereal-legume mixed batters as influenced by process parameters during preparation of dhokla and idli, traditional steamed pancakes

Abstract: Dhokla and idli are popular breakfast foods in India. The objective of the present study was to evaluate their antioxidative properties during different stages of preparation. The effects of fermentation on the enhancement of antioxidative activities were reflected by a higher total phenol content (TPC) in the fermented batters, which also displayed better antioxidative activities than their unfermented batters and steam-cooked products. Fermentation enhanced>2.5-fold TPC and>125% reducing activity. The fermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…The FRAP value was concentration dependent and ranged from 0.07 to 0.79 mmol Fe 2+ /mg, a significant variation in reducing activity of the biscuit extracts was observed and the pigeon pea supplemented biscuits (APC1 and APC2) exhibited higher FRAP values than non‐supplemented biscuits (BCC and ACC). The ability to reduce Fe 3+ to Fe 2+ by the cracker biscuits increased with increase in supplementation with pigeon pea flour which may be attributed to the ability of incorporated pigeon pea flour to form reductants that could react with the free radicals thereby stabilizing and terminating the radical chain (Moktan, Roy, & Sarkar, ). The significantly ( p < 0.05) higher antioxidant properties observed in the formulated biscuits compare with market sample (BCC) may be attributed to the cereal choice as well as legume flour incorporation which contributed potential bioactive properties to the snacks.…”
Section: Resultsmentioning
confidence: 99%
“…The FRAP value was concentration dependent and ranged from 0.07 to 0.79 mmol Fe 2+ /mg, a significant variation in reducing activity of the biscuit extracts was observed and the pigeon pea supplemented biscuits (APC1 and APC2) exhibited higher FRAP values than non‐supplemented biscuits (BCC and ACC). The ability to reduce Fe 3+ to Fe 2+ by the cracker biscuits increased with increase in supplementation with pigeon pea flour which may be attributed to the ability of incorporated pigeon pea flour to form reductants that could react with the free radicals thereby stabilizing and terminating the radical chain (Moktan, Roy, & Sarkar, ). The significantly ( p < 0.05) higher antioxidant properties observed in the formulated biscuits compare with market sample (BCC) may be attributed to the cereal choice as well as legume flour incorporation which contributed potential bioactive properties to the snacks.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds in fermented pulses have been documented to exhibit antioxidant properties. As reported by Moktan et al [61], idli and dhokla exhibited metal chelating, lipid peroxidation, and high free radical-scavenging activities. Likewise, common bean and tempeh products exhibited radicalscavenging and antioxidant activities.…”
Section: Phenolic Compoundsmentioning
confidence: 59%
“…Joshi et al (1989) reported that dhoklas prepared from fermented mixture of Bengal gram and curds which exhibited the best sensory qualities comprised several volatile acids including propionic acid, isobutyric acid, isovaleric acid, and acetoin. The antioxidant property of fermented dhokla batter is reported to be high, and this helps in curing age-related diseases and oxidative stress-induced degenerative diseases (Moktan et al 2011). So, dhokla can be a good food item for the diabetic patients.…”
Section: Dhoklamentioning
confidence: 99%